DriveLEDs: software for synchronous control and video acquisition of fluorescent signals - Zakharov, Andrey; Ponomareva, Daria; Petukhova, Elena; Bregestovski, Piotr (Frontiers in Physics, 2023)
Current research uses various fluorescent biosensors to measure ion concentrations, neuronal activity, or cellular components in biological preparations. Several free solutions are available to researchers for recording or analysing fluorescent signals. However, when using different software packages, there are great difficulties in converting data between them. Problems also arise with linking and coordination of individual hardware devices into a single measurement system. Our paper presents useful software that allows to avoid most of these problems. It enables the recording, online visualization and preliminary analysis of fluorescent signals in brain cells and other experimental models. We describe and test software optimized for ratiometric measurements. The program selects device operating modes that allow reliable changes in illumination wavelength, camera image capture, and online graphical visualization of fluorescent signal amplitudes or ratiometric data. The performance of the software was successfully tested on mouse brain using two experimental models; (i) simultaneous monitoring of intracellular chloride and hydrogen in transgenic mice expressing genetically encoded biosensor; (ii) recording changes in reactive oxygen species during synaptic stimulation of neurons in mouse hippocampal slices. This software allows to overcome the incompatibility of the devices used and reduce the cost of experimental measurements. The software is completely original, easy to use and may be of interest to many scientists involved in the analysis of light-controlled signals in a variety of experimental models, including drug screening, epilepsy models, and other applications. The software is open-source product and can be obtained via GitHub: https://github.com/AndreyZakharovExp/DriveLEDs